33 Influence of age of dam on daughter reproductive performance and follicle numbers in beef heifers. (30th November 2020) - Cushman, Robert; Spuri-Gomes, Renata; Tenley, Sarah; Rosasco, Shelby; Rich, Jerica; Northrop, Emmalee; Miles, Jeremy; Lindhom-Perry, Amanda; Keel, Brittney; Perry, George; Summers, Adam; Cupp, Andrea
Abstract: Heifers born to heifers have fewer primordial follicles in their ovaries at a year of age than heifers born to mature cows. We, therefore, hypothesized that heifers born to heifers would have decreased reproductive efficiency compared to heifers born to mature cows. Data were extracted from the USMARC database for replacement heifers (n = 7053) born between 2003 and 2010, representing 4631 dams. Ovaries were collected from neonatal (< 20 d) heifers born to heifers (n = 53) or heifers born to mature cows (n = 96) to examine influence of age of dam on follicle numbers immediately after birth. Data were analyzed using the MIXED procedure of SAS with age of dam as a class effect. For production data, dam was a random effect to account for dams having more than one daughter represented in the data. Heifers born to dams less than 6 years of age produced fewer calves than heifers born to cows greater than 5 years of age (5.2 ± 0.1 or 5.5 ± 0.1 calves, respectively; P < 0.0001). Heifers born to heifers weighed less at birth and weaning than heifers born to mature cows (P < 0.0001). Age of dam, however, did not influence number of antral follicles in the ovaries of neonatal heifers between heifers born to heifers and heifers born to mature cows (9.6 ± 1.4 and 8.0 ± 1.0; P = 0.36). As hypothesized, age of dam influences daughter reproductive performance; however, this does not appear to be completely driven by mechanisms associated with size of the ovarian reserve. Divergence in number of follicles in the ovaries does not occur until after 1 month of age, but this could be a carry-over effect of intra-uterine growth restriction in heifers born to heifers. USDA is an equal opportunity provider and employer.